Energy and Exergy Analyses of Egyptian Cement Kiln Plant with Complete Kiln Gas Diversion through by Pass - Laila M. Farag (Institute of Advanced Engineering and Science, 2012)
The present article deals with evaluation of energy and exergy efficiences of an Egyptian dry process cement kiln plant with precalciner characterized by that the whole kiln gas is diverted through by pass . Such diversion is necessary to break the intense cycles of secondary constituents Cl, alkalis and sulfur that may arise between precaciner -preheater and kiln due to the high content of the raw materials of such secondary constituents. Based on average actual operation data of the process, energy and exergy balances have been established around the preheater-precalciner, the rotary kiln , the rotary cooler and the whole process. Energetic- and exergetic efficiency of the process attains 40% and 25.7% respectively . Sum of the exergy outputs attains about 49% of total exergy input and irreversibility loss = 2354 kJ/kg clinker which represents about 51 % of total exergy input. Energy and exergy of the by pass gases are the largest output loss items ( 770 and 416 kJ/kg cli respectively) followed by those of the preheater exit gases ( 622 and 152 kJ/kg cli respectively). For comparative purpose , the process was evaluated with considering no diversion of kiln gas through by pass . Energetic- and exergetic efficiency has been estimated in this case as 52% and 34 % respectively and the irreversibility attains 1840 kJ/kg clinker which represents about 52 % of total exergy input.